Effect of side groups on the vacuum thermal evaporation of polythiophenes for organic electronics - Kovacik, P; Willis, S; Matichak, J; Assender, H; Watt, A (2012)
The vacuum thermal evaporation of poly(3-hexylthiophene) (P3HT) and poly(thiophene) (PTh) conductive polymers with and without side groups is reported. The role of side groups in relation to structural and electronic properties is examined. FT-IR and GPC analysis is used to study the effect deposition has on conjugation of the polymer. Topography and grain structure of the polymer films are studied using MicroXAM, AFM and TEM. XRD and TEM data reveal enhanced molecular packing and crystallinity of PTh. This results in significantly improved charge transport properties with relatively high hole mobilities (10 -4 cm 2/Vs). Evaluation of PTh and P3HT electronic properties is performed on simple geometry planar C 60 heterojunction solar cells. PTh/C 60 devices exhibit almost a 70% increase in efficiency as compared to P3HT/C 60 devices, demonstrating enhanced charge collection in PTh films through improved molecular order. © 2012 Elsevier B.V. All rights reserved.